Material analysis versus historical dye recipes: ingredients found in black dyed wool from five Belgian archives (1650-1850) - Natalia Ortega Saez; Ina Vanden Berghe; Olivier Schalm; Bert De Munck; Joost Caen (Conservar Património, 2019)
The relationship between bibliographic and archival research, on the one hand, and object-based study, on the other, forms a very important basis for research into historical production techniques. Several written sources provide insight into the recipes for dyeing black in the past. Yet, this does not guarantee that these written recipes are representative of an entire society or were used in the dyers practice. The way to assess how closely practical dyeing and written sources are aligned entail the chemical analysis of historical textiles. This article focuses on the identification of the ingredients used to dye wool black in the case of well-preserved and dated (1650-1850) historical textiles from five Belgian archives and some remaining historical artefacts. The results are compared with the technical knowledge of dyeing and the ingredients mentioned in written sources from the same period. The aim is to refine the knowledge of the different black dye ingredients used in practice in Northwest Europe during the period.